Analysis of Clinical Experience Using Kolb’s Experiential Learning Theory: Postgraduate Medical Surgical Nursing Track Students in Selected Sub-Specialties at the University Teaching Hospital of Kigali, Rwanda - Bagweneza, Vedaste; Anita, Collins; Nsanzamahoro, Isaac; Mukanoheli, Vestine; Bahaya, Florian; Niyitegeka, Perpetue; Kabanyana, Pauline; Mwiseneza, Marie Josee; Gaterega, Tony; Kura, Agnes; Twahirwa, Claude; Munezero, Marie (Rwanda journal of medicine and health sciences, 2021)
BackgroundClinical experiences provide an opportunity for nursing students to integrate theoretical knowledge into practice, and analyze their learning using a theoretical model. Students do not take this opportunity unless it is intentionally included by the facilitators. These observations from the second cohort of medical surgical nursing students with their facilitators, regarding their clinical training period in selected sub-specialties at the University Teaching Hospital of Kigali (CHUK) aimed at developing students’ analytical and observational skills while developing clinical skills.MethodsThe study involved nine medical surgical nursing students who were in different subspecialties at CHUK from 7th January up to the 20th February, 2019. Informed observational approach and concomitant reporting were used to validate their learning and gain clinical experience. The students used Kolb’s Experiential Learning Theory to analyze their experience, with the focus on innovative skills.ResultsAll medical surgical nursing students reported that they improved their knowledge and skills during clinical practice, while broadening their outlook.ConclusionKolb’s Experiential Learning Theory is useful in validating and bridging theoretical learning to clinical practice.Rwanda J Med Health Sci 2021;4(3):430-436